DISTRIBUTION OF TROPICAL EEL GENUS Anguilla IN INDONESIA WATER BASED ON SEMI-MULTIPLEX PCR - Melta Rini Fahmi; Laurent Pouyaud; Patrick Berrebi (Indonesian Aquaculture Journal, 2012)
Tropical eels living in Indonesian waters are known to be composed of several species, but their real listing together with their distribution ranges need to be established. The main difficulties are the very high number of islands with perennial rivers where these species are living during the growth phase of their life cycle. It is difficult, sometimes impossible, to determine the species using morphological characters, moreover on glass eels. In order to establish the geographic distribution of tropical eels of the genus Anguilla in Indonesian waters, a total 1,115 specimens were collected between 2008 and 2012. Sample collection was done in the growth habitats that are rivers and estuaries by commercial nets of different categories according to the fish size. All samples were identified genetically using the recently developed semimultiplex PCR method. We recognized four species and subspecies with wide distribution: Anguilla bicolor bicolor, Anguilla bicolor pacifica, Anguilla marmorata, and Anguilla interioris; two species with limited distribution, close to endemism: Anguilla celebesensis and Anguilla borneensis and one subspecies Anguilla nebulosa nebulosa that is only spread in river flowing into Indian Ocean.